Dietary supplement intake and perception assessment among adolescent athletes - Mohd Hamzah, Miza Karmila; Azhar, Ikmal Hakimi; Abdullah, Muhamad Arif; Mustafa, Norashikin (IIUM Press, 2023)
Introduction:Studies have shown that athletes often have inadequate micronutrient intakes, and the use of dietary supplements can help address these deficiencies.However, most of the dietary supplement studieswerefocusing on adult and elite athletes. Thus, this study aimedto identify the prevalence and perception of dietary supplement intake among adolescent athletes in Kuantan, Pahang.Method: The study was conducted using a cross-sectional design among106 athletics and team sports athletes(72.6% male;14.6 +1.4 years old) The respondents were asked to complete a Dietary Supplement Prevalence and Perception Assessment Questionnaire(DSPAQ) which consisted of items on their demographic information, dietary supplement intake and perception. The prevalence dietary supplement intake between athletics and team sports was statistically analysed and the significance was ascertained using Chi-square test.Result: The overall prevalence of dietary supplements intake among athletes was 9.4 % with protein supplements being the predominant supplement (71%). The main reasons for the consumption of dietary supplements were to improve muscle strength, performance and maintain health. However, the prevalence was not associated to the type of sports. The adolescent athletes had a perception that they need more supplement information and believe supplement can enhances their performance.In addition,the main reason for not taking dietary supplements was related to the cost. Conclusion: In conclusion,adolescent athletes in this study areprone to not taking dietary supplements with the perception of needing more information about the supplement